NILAI-NILAI PENDIDIKAN ISLAM DALAM SENI KALIGRAFI AL-QUR’AN - Suharno Suharno; Asrori Mukhtarom (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2021)
This study seeks to determine the values of Islamic education contained in the art of writing the Al-Qur'an Mushaf calligraphy. The research method used in this research is literature study, by gathering information relevant to the topic being the object of research. This information can be obtained through books, journals, dissertations, and other sources. The results of this study show that there are values of Islamic education in the art of calligraphy, such as the value of love for the Qur'an, the value of hard work behavior, the value of patience, and the value of optimism. The values of Islamic education are very important to be implemented by students in everyday life. Therefore in the implementation of Islamic education it is necessary to include calligraphy art material in the Islamic education curriculum.